Urban vs. Rural: food choice analysis and its association with nutritional status and academic achievement among adolescents - Fakhiratunnisa Putri Oceani; Ikeu Tanziha; Drajat Martianto (AcTion: Aceh Nutrition Journal, 2025)
Long-term food choices influence dietary patterns, contribute to the nutritional status of adolescents, affect cognitive function, and affect academic achievement. This study provides a novel perspective by examining food choices across urban and rural settings, an area seldom explored in the Indonesian context, and their association with adolescents' nutritional status and academic performance. This study employed a cross-sectional design to capture the relationship among food choice, nutritional status, and academic achievement at a single point in time. in November–December at two schools, Senior High School 1 Dramaga as an urban area and Senior High School 1 Nanggung as a rural area, involving 377 subjects. The collected data included nutritional status using anthropometric measurements, food choice analysis using FCQ, and academic achievement using final exam results. Data analysis included univariate methods, bivariate Spearman's rank correlation, and the Mann–Whitney U test to assess differences between the two study areas. This study showed that there is a correlation between food choice and nutritional status. In urban areas, the results were significant (p=<0,001) for health (r=0,732) mood (r= -0,592), convenience (r= -0,509), sensory appeal (r= -0,223), familiarity (r= 0,570), and weight control (r= 0,708). In rural areas, there were significant differences (p<0,001) in (r= 0,610), mood (r= -0,473), sensory appeal (r= -0,409), natural content (r= 0,577), price (r= 0,571), familiarity (r= 0,582), and weight control (r= 0,690).. Moreover, nutritional status was positively correlated with academic achievement (p < 0,001) in urban (r= 0,741) and rural areas (r=0,525). In conclusion, food choice significantly affects adolescents’ nutritional status and academic achievement in urban and rural areas. Therefore, structured education on the importance of making food choices based on health considerations and nutritional content is essential as a strategic effort to improve long-term nutritional status and academic performance.